2014
DOI: 10.1002/ppap.201400057
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Morphogenesis of Needle-Like and Multibranched Structures in Maleic Anhydride Plasma Polymer Thin Films

Abstract: We report for the first time the formation of spherical and branched structures when polymerizing maleic anhydride under very low power with pulsed plasma polymerization. A factorial experimental design evidenced duty cycle, frequency and their interactions as decisive factors for the formation and growth of these structures. A mechanism involving the decoupling of deposition (nucleation) and diffusion rates of active species was proposed to relate structure formation to processing parameters. While difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…In previous work, we reported the possibility of obtaining nanostructured MAPP surfaces depending on the experimental parameters employed during the plasma polymerization process. In addition to establishing the experimental conditions for the formation of these structures, a formation mechanism was proposed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, we reported the possibility of obtaining nanostructured MAPP surfaces depending on the experimental parameters employed during the plasma polymerization process. In addition to establishing the experimental conditions for the formation of these structures, a formation mechanism was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma was initiated through a high‐frequency generator of P p . The condition used for the deposition was 20 W, 2% DC, and 204 Hz, since at this condition the differentiation and development of structures were easily observed . Different times of deposition were performed in order to analyze the growing kinetics of the structures, resulting in the samples MAPP‐2, MAPP‐5, MAPP‐10, MAPP‐15, MAPP‐20, MAPP‐30, MAPP‐50, and MAPP‐90, where the numbers represent the time of deposition in minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5−11 Likewise, different nanoscale morphologies have been recently reported in a maleic anhydride plasma polymer (MAPP) prepared through pulsed excitation. 12,13 Beads, branched, and needlelike complex nanostructures were for the first time observed in this system and found to depend on plasma parameters, namely, peak power, duty cycle, frequency, and time. 12,13 The possibility to tune MAPP morphology beside the well-established tunability of MAPP chemistry 22−25 further increases the attractivity of MAPPs for various applications 14−16 and particularly as platforms for biosurface engineering.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Indeed, for most of synthesis conditions, PPF are pinhole‐free and perfectly smooth, thus, limiting further development in this field based on the previous considerations about the importance of nanostructuring organic‐based coatings. For sake of completeness, it should, however, be noted that recent studies have demonstrated that under specific conditions, PPF exhibit complex nanostructured morphology (e.g., petal/dome‐like nanostructures, nano‐pillars, nano‐ribbons, nano‐columns, or nanoporous coating) . Nevertheless, the availability to tailor the size, the shape, and the length of the nano‐structures is strongly limited and highly challenging.…”
Section: Introductionmentioning
confidence: 99%